A race from the bottom? Lessons from a workers' struggle at a Bangalore warehouse. (August 2019) - Kumar, Ashok
This paper analyses the emergence of the 'full package' firm in India and its implications for workers' strategies. A 'full package' firm expands outward, from low-value assembly-only products to high-value specialized garment production; consolidating under one roof. Historically, geographic and political barriers separated centres of value-creation (producers) and value-capture (brands and retailers) in the global garment sector. However, enhanced value-capture at the point of production has led to considerable consolidation organizationally, giving an increasingly symbiotic character to relationships within 'buyer driven' supply chains. Though this change aggregates the bargaining power of workers, it also introduces new obstacles to workers' organization. The concomitant rise of supplier-end value capture allows garment trade unions to nonetheless demand greater shares. Thus, previously unviable modes and methods have become available to workers engaged in struggles with their employers in the globalized garment sector. This paper examines a protracted workers' struggle in light of this process. In doing so, the paper demonstrates that codes of conduct and auditing alone cannot significantly impact labour standards because the needs of capital accumulation are greater than the threat posed by any auditing program or code. Ultimately, the paper demonstrates that labour rights within the garment GVC will not arrive through a rights-based approach – though strong codes of conduct and independent auditing can assist – but rather through a combination of an increased power of suppliers vis-à-vis buyers, greater workers' bargaining power with their direct employers, and – critically – workers' self organization.